Behavioral Intentions towards adoption of Information Protection and Cyber security (Email Security and Online Privacy): SEM model (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Email security and online privacy have become the hot-spots of discussion during the testing times of the pandemic as most of the communication and transactions take place through email and online respective-ly. Though the industry of information security claims to have put forth rigorous rules and guidelines to contin-ually ensure and improve the level and quality of Email security and online privacy, the people always have their own doubts and fears about the same. The doubts and the fears appears to have increased with the wide-spread pandemic as the people who are new to email communication and online transactions are compelled to involve in them. With this as the backdrop, the researchers aim to analyze the level of confidence created by the existing Email security and online privacy standards by identifying the people’s opinions, their beliefs and their trust towards them. In order to arrive at the above, a survey, using a structured questionnaire, was con-ducted among six-hundred people, residing in the Asia-pacific region, selected using convenient sampling. The data were collected and analyzed. The results indicate that the human intentions, beliefs and trust have a great influence on Cyber defenses (Email Client Security and Online Privacy) in this region. The study also provides information on the outstanding nature of these measurement items and the perception of privacy and security in information sharing as distinctive constructs